American Joint Committee on Cancer eighth edition human papilloma virus positive oropharyngeal cancer staging system: Discordance between clinical and pathological staging systems. Issue 8 (2nd April 2019) - Hall, Scott R.; Neel, Gregory S.; Chang, Brent A.; Howard, Brittany E.; Nagel, Thomas H.; Lott, David G.; Hayden, Richard E.; Zhang, Nan; Hinni, Michael L.
Abstract: Background: The American Joint Committee on Cancer (AJCC) eighth edition introduces a staging system specific for human papilloma virus positive oropharyngeal cancer with separate clinical (AJCC 8c) and pathological (AJCC 8p) criteria. Methods: In this retrospective cohort study, preoperative imaging and pathology reports were used to stage patients based on the AJCC 8c and AJCC 8p criteria, respectively. The primary endpoint was agreement between AJCC 8c and AJCC 8p. Results: A total of 213 patients met inclusion criteria. Kappa statistics showed poor agreement ( κ = 0.3275) between AJCC 8c and AJCC 8p. In total, 30.3% of patient's preoperative AJCC 8c stage changed based on the postoperative pathologic staging (AJCC 8p) with 73.4% of those being upstaged. Conclusion: These data suggest that disagreement exists between AJCC 8c and AJCC 8p, in part due to the separate clinical and pathological staging criteria. This discrepancy should be considered as the new system is implemented.